2009
DOI: 10.1021/jf901471c
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Ammonia-Lyase, Polyphenol Oxidase, and Phenol Concentration in Fruits ofOlea europaeaL. cv. Picual, Verdial, Arbequina, and Frantoio during Ripening

Abstract: The kinetics and protein-expression level of phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO) in fruits of olive trees (Olea europaea) cv. Picual, Verdial, Arbequina, and Frantoio have been studied in relation to the concentration of total phenolic compounds, oleuropein, hydroxytyrosol, and tyrosol during fruit ripening. Frantoio was the variety that showed the highest total phenol concentration, the highest PAL activity, the lowest PPO activity, and the lowest protein levels. In contrast, Verdia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
3
20
0
2
Order By: Relevance
“…Analyzing the results for EVOOs at different harvest dates, we found that the decrease in decarboxymethyl oleuropein aglycone and decarboxymethyl ligstroside aglycone content during ripening was accompanied by an increase on their hydroxylated forms. These results could be explained by the rise in the activity of polyphenol oxidase at more advanced ripening stages, previously reported in the literature [29]. It should be taken into account that these compounds could also be produced during the olive-oil extraction process (crushing and malaxation steps), which may change their concentration in the final product (olive oil) [30].…”
Section: Quantitative Characterizationmentioning
confidence: 60%
“…Analyzing the results for EVOOs at different harvest dates, we found that the decrease in decarboxymethyl oleuropein aglycone and decarboxymethyl ligstroside aglycone content during ripening was accompanied by an increase on their hydroxylated forms. These results could be explained by the rise in the activity of polyphenol oxidase at more advanced ripening stages, previously reported in the literature [29]. It should be taken into account that these compounds could also be produced during the olive-oil extraction process (crushing and malaxation steps), which may change their concentration in the final product (olive oil) [30].…”
Section: Quantitative Characterizationmentioning
confidence: 60%
“…Therefore, it is essential to identify the harvest period that will ensure a ripening stage corresponding with optimal phenolic content. There is a general consistent trend of reduction in polar phenol levels as the fruit matures in various cultivars and environments, such as Picual, Hojiblanca, Verdial, Arbequina, and Frantoio in Spain [8,[17][18][19][20], and Barnea and Souri in Israel [12]. This decrease in total polar phenol content is attributed mainly to the decline in oleuropein occurring as part of the physiological maturation of the fruit [21].…”
Section: Total Polar Phenol Contentmentioning
confidence: 76%
“…So far there is very few information regarding this subject in olive (Olea europaea). Several studies have partially purified, characterized and identified the cellular location of PPO and POX in olive fruits (Ben-Shalom et al, 1977;Lopez-Huertas and Del Rio, 2014;Saraiva et al, 2007;Shomer et al, 1979;Tzika et al, 2009) and both POX and PPO activities have been investigated during unrelated processes such as browning (Goupy et al, 1991;Sciancalepore and Longone, 1984;Segovia-Bravo et al, 2007) and ripening (Ebrahimzadeh et al, 2003;Ortega-García et al, 2008;Ortega-García and Peragón, 2009).…”
Section: Role Of Oxidative Enzymesactivity and Isoformsmentioning
confidence: 99%